Honey As Complementary Medicine: A Review - M P SINGH; HEMANT RAMESH CHOURASIA; MANISH AGARWAL; AKHIL MALHOTRA; MUKESH SHARMA; DEEPAK SHARMA; SHEEBA KHAN (International Journal of Pharma and Bio Sciences, 2012)
Honey is a natural sweetener, but it is not just a sweetener it’s a nature’s gift to mankind. Natural honey has various ingredients in it, that contribute to its incredible properties. It’s antimicrobial properties have attracted researchers towards itself and now we can find many research papers published on this topic. Honey is normally used in our daily life for treatment of hearing loss, bad breath, fatigue, weight loss, pimples, influenza, ingestion, heart diseases, toothache, hair loss, bladder infections, infertility etc. Honey is used as a mixture with many natural products such as lemon, clover, milk, cinnamon and water for treatment of various ailments and other health disorders. Beside this, honey is now used in various industries that exploit nature’s wonderful gift (honey). Commercially honey is used as moisturizer, hair conditioner, laxative, aphrodisiac, rooting hormone, cleansers etc. Honey mixed with ground almonds makes an excellent facial cleansing scrub.